2016
DOI: 10.1111/tpj.13241
|View full text |Cite
|
Sign up to set email alerts
|

Mutations in the N‐terminal kinase‐like domain of the repressor of photomorphogenesis SPA1 severely impair SPA1 function but not light responsiveness in Arabidopsis

Abstract: The COP1/SPA complex is an E3 ubiquitin ligase that acts as a key repressor of photomorphogenesis in dark-grown plants. While both COP1 and the four SPA proteins contain coiled-coil and WD-repeat domains, SPA proteins differ from COP1 in carrying an N-terminal kinase-like domain that is not present in COP1. Here, we have analyzed the effects of deletions and missense mutations in the N-terminus of SPA1 when expressed in a spa quadruple mutant background devoid of any other SPA proteins. Deletion of the large N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 64 publications
2
15
0
Order By: Relevance
“…We found that COP1 preferentially interacts with the phosphorylated, higher-mobility isoforms of CRY1 and CRY2 that are formed upon B-irradiation. A similar observation was made for the B-dependent association of SPA1 and SPA2 with the higher-mobility isoforms of cryptochromes [ 26 , 37 ]. The B-induced phosphorylation of cryptochromes is a key step in cryptochrome activation and function [ 5 ].…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…We found that COP1 preferentially interacts with the phosphorylated, higher-mobility isoforms of CRY1 and CRY2 that are formed upon B-irradiation. A similar observation was made for the B-dependent association of SPA1 and SPA2 with the higher-mobility isoforms of cryptochromes [ 26 , 37 ]. The B-induced phosphorylation of cryptochromes is a key step in cryptochrome activation and function [ 5 ].…”
Section: Discussionsupporting
confidence: 73%
“…These experiments were performed as described in [ 37 ]. Briefly, seedlings were homogenized in extraction buffer (50 mM Tris pH 7.5, 150 mM NaCl, 1 mM EDTA, 10% glycerol, 0.1% Triton X-100, 5 mM DTT, 1% protease inhibitor cocktail (Sigma-Aldrich), 10 μM MG132, phosSTOP phosphatase inhibitor cocktail (Roche, 1 tablet/5 ml buffer)).…”
Section: Methodsmentioning
confidence: 99%
“…LUMIER protein-protein interaction assays in mammalian HEK293 cell culture was performed as described in (Holtkotte et al, 2016).…”
Section: Coimmunoprecipitations and Immunodetection Of Proteinsmentioning
confidence: 99%
“…It has been suggested that the kinase domain of SPA1 may provide structural information critical for SPA1 function (Holtkotte et al, 2016). SPA1 R517E mutant shows a defect in PIF1 degradation and seed germination in response to light (Paik et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…SPA1 kinase domain is conserved in SPA1 sequences from multiple plants (Paik et al, 2019). The R517 residue in SPA1 is part of a conserved Glu-Arg salt bridge that defines eukaryotic protein kinases (Yang et al, 2012) and has recently been shown to be critical for its biological function in the dark (Holtkotte et al, 2016). To investigate the importance of SPA1-Ser/Thr kinase activity for HY5 phosphorylation, we used the point mutant version of SPA1 (mSPA1) that has the R517E mutation in the kinase domain.…”
Section: Spa1 Kinase Domain Is Essential For Its Kinase Activity and mentioning
confidence: 99%